The Effect of Viral Marketing on Purchase Decision with Customer Trust as Intervening Variable - Rio Garia Aprillio; Arry Widodo (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
The study aims to determine the level of influence of viral marketing on purchasing decisions through customer trust in favehotel Hyper Square Bandung. The condition shows more eagerness on their business, the more enhancement on its services. The variables in this study are viral marketing as an independent variable, purchasing decision as a dependent variable, and customer trust as an intervening variable. The used method of this study was a quantitative method with the type of research of descriptive associative with a sample of 400 respondents. The used sampling technique in this study was non-probability sampling. The used methods of data analysis in this research were descriptive analysis method and structural equation modeling (SEM). Data processing was performed by using SmartPLS 3.0 software for Windows. Research Result: (1) Viral marketing variable (X) has an influence significant with intervening variables of customer trust (Z). (2) The effect of intervening variable customer trust (Z)hasn an influence significant on purchase decision (Y). (3) The effect of viral marketing (X) has an influence significant on purchase decision (Y). (4) The indirect effect between viral marketing (X) and purchase decision (Y) through intervening variable customer trust (Z) has a positive indirect effect of 0.296 and t-statistics value of 9.950> 1.96, which means significant.